Barriers to delivery of culturally competent care among nurses: A multi-center cross-sectional study in a resource-limited setting - Abdul-Karim Abubakari; Janet Gross; Eric Asamoah (Elsevier, 2024)
Background: In a growing multicultural society like Ghana, the cultural competence (CC) of nurses is imperative. Despite the importance of CC within the healthcare environment, factors that hinder nurses' ability to render culturally competent care (CCC) to patients in the clinical unit have not been adequately explored. Purpose: To examine the barriers nurses encounter in the delivery of CCC across two regions of Ghana. Methods: From October to December 2022, an institutional-based cross-sectional study in eight hospitals involving nurses was conducted in the Western and Ashanti regions. A probability sampling method was employed to select 759 participants. Data was entered into a spreadsheet and exported to S.P.S.S version 23. Binary and multivariable logistic regressions were used to establish the associations between dependent and independent variables. The odds ratio with a 95 % confidence interval was computed. Outcome variables with a P-value < 0.05 were deemed statistically significant. Results: The majority of the respondents were females (61.4 %; n = 466). The three-factor structure of the instrument was validated using an exploratory factor analysis. The study revealed that barriers that hindered nurses were the lack of CCC policies (β = 0.150, 95 % CI = 0.120, 0.180), nurse staffing-related factors (β = 0.120, 95 %; CI = 0.090, 0.150), and the lack of training related factors (β = 0.084, 95 % CI = 0.054, 0.114). Nurses' age, marital status, and experience were significant at a p-value of < 0.05. Conclusion: The lack of culturally appropriate policies, lack of training-related factors, and nurse staffing-related challenges hindered respondents' efforts to render CCC. Interventions aimed at improving CCC should target these barriers.